Use of Geotextiles Baffle Contact Method for Biomass Development in Treatment of Domestic Wastewater - Ramesh S. T.; Gandhimathi R.; Nidheesh P. V.; Satyanarayana Rao P. (International Journal of Research in Chemistry and Environment (IJRCE), 2012)
Use of geotextile baffles as biofilm attachment media for wastewater treatment has been carried out in the present study. This Geotextile Baffle Contact System (GBCS) reactor was operated at different ydraulic Retention Time (HRT) of 24hr, 18hr, 12hr, 8hr and 6hr in room temperature. The removal of Chemical Oxygen Demand (COD) was monitored for different ydraulic Retention Time (HRT) and Organic Loading Rates (OLR). For Hydraulic Retention Time (HRT) of 24hr and OLR of 0.31 COD/m3/day, 84% COD removal efficiency has been achieved. For ydraulic Retention Time (HRT) of 18hr and OLR of 0.41 COD/m3/day, 82% COD removal efficiency has been obtained. As Organic Loading Rates (OLR) increases the COD removal efficiency decreases. Overall the Geotextile Baffle Contact System (GBCS) system is an efficient tool for wastewater treatment.